Role of church-based organizations in the care of widowed older adults in Enugu State, Nigeria - Okwor, Christopher O. (Journal of religion, spirituality & aging, 2026)
Spousal death usually leads to social, emotional, economic, and health breakdown. This is worrisome in Nigeria with respect to older adults consequent upon poor formal care systems. The study ascertained the roles of church in the care of widowed older adults. Qualitative data were collected from 28 widowed aged 60 and above using Focus Group Discussion and In-depth Interview. The data were analysed thematically. Church-based organizations are not inactive in supporting widowed older adults rather these individuals are coerced to make financial contribution amidst numerous challenges. Church leaders are urged to prioritize the care of widowed older adults.